CRISPR/Cas9 mutagenesis reveals an essential role of PI4KB in promoting growth and resisting hemorrhagic disease caused by GCRV-II infection in juvenile grass carp - Jie Zhang; Liqiang Zhang; Xiaoman Wu; Minhui Tao; Yang Chen; Mingxian Chang (Water Biology and Security)
Few studies have reported obtaining grass carp resistant to hemorrhagic disease via gene editing in commercial fish. Here, we demonstrate that the expression and activity of grass carp PI4KB (gcPI4KB) are vital for GCRV-I and GCRV-II replication. Given the obvious cytopathic effect (CPE) in the present available cell lines is only caused by GCRV-I, but GCRV-II is the current popular and fatal strain in grass carp, GCRV-I and GCRV-II are used in cell lines and in grass carp, respectively. In vitro studies in CIK cells revealed that gcPI4KB interacted with NS80 and VP3 of GCRV-I, and that gcPI4KB was recruited by NS80 for promoting the generation of GCRV viral inclusion bodies (VIBs). Since the negative regulatory role of gcPI4KB in GCRV infection was confirmed by in vitro data, we performed gene editing of gcPI4KB in grass carp. We found that PI4KB F0 juvenile grass carp crispants have obvious advantages in promoting growth and in resisting GCRV-II infection. Compared with uninfected WT grass carp, the uninfected PI4KB F0 juvenile grass carp crispants exhibit a higher expression level of many genes involved in growth- and development-related metabolic pathways such as the FoxO signaling pathway and insulin signaling pathway. Compared with WT grass carp without infection, PI4KB F0 juvenile grass carp crispants without infection or WT grass carp infected with GCRV-II, higher expression levels for many genes involved in metabolic diseases and viral infections were observed in the liver from PI4KB F0 juvenile grass carp crispants infected with GCRV-II. Altogether, the present study suggests the mechanism of gcPI4KB in facilitating GCRV replication, the signaling pathways regulated by gcPI4KB, and the possibility to obtain grass carp resistant to hemorrhagic disease via gene editing of PI4KB.